Preparation method of high-toughness, high-corrosion-resistance, high-chromium and high-molybdenum ferrite stainless steel

By adding Nb and Cu elements to high-chromium high-molybdenum ferrite stainless steel, the Si content is controlled, and low-temperature hot rolling and recrystallization annealing process is adopted to suppress brittle phase precipitation and promote nano-scale Laves phase precipitation, solving the problem of poor corrosion resistance of the material in Cl ion environment, and achieving high strength and high corrosion resistance.

CN119506734AActive Publication Date: 2025-02-25ZHONGBEI UNIV

Patent Information

Application Number
CN202411753663.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-02
Publication Date
2025-02-25
Estimated Expiration
2044-12-02

AI Technical Summary

Technical Problem

High chromium high molybdenum ferrite stainless steel is prone to precipitation of brittle phases during the preparation process, resulting in the deterioration of the strength and corrosion resistance of the material, especially in the Cl ion environment, which shows poor corrosion resistance.

Method used

By adding appropriate amounts of Nb and Cu elements to ferrite steel, the Si element content is controlled, and suitable production processes are adopted to inhibit the precipitation of σ and χ brittle phases, promote the precipitation of nano-scale Laves phases, avoid the precipitation of Cu-rich phases, realize low-temperature hot rolling and recrystallization annealing, refine the grains, and improve the strength and corrosion resistance of the material.

Benefits of technology

High-strength, high-corrosion resistance, high-chromium, high-molybdenum ferrite stainless steel has a yield strength of 560-660MPa, a tensile strength of 670-770MPa, and an elongation after break of 23-27%, showing significant pitting resistance under Cl ion environment.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119506734A_ABST
    Figure CN119506734A_ABST
Patent Text Reader

Abstract

The invention relates to ferritic stainless steel, in particular to a preparation method of high-toughness, high-corrosion-resistance, high-chromium and high-molybdenum ferritic stainless steel. The invention aims to provide a method for preparing high-chromium and high-molybdenum ferritic stainless steel with high strength and toughness and high corrosion resistance, namely a preparation method of the high-chromium and high-molybdenum ferritic stainless steel with high strength and toughness and high corrosion resistance, which comprises the following steps: adding a proper amount of Cu element into the high-chromium and high-molybdenum ferritic stainless steel, and controlling the content of Si element, thereby obtaining the high-chromium and high-molybdenum ferritic stainless steel with high strength and toughness and high corrosion resistance. Nb element single stabilization is adopted, and a proper production process is selected, so that the yield strength, the tensile strength, the percentage elongation after fracture and the corrosion resistance are remarkably improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of high-chromium and high-molybdenum ferrite stainless steel, and in particular to a method for preparing high-strength and high-toughness, high-corrosion-resistant high-chromium and high-molybdenum ferrite stainless steel. Background Art

[0002] High-chromium and high-molybdenum ferritic stainless steel has high corrosion resistance, high strength, good thermal conductivity, low expansion and other excellent comprehensive properties due to its high Cr and Mo content. It is mainly used as a low-cost heat exchange material in corrosive environments, such as replacing copper tubes and titanium tubes to manufacture condensers for XX power stations. Condensers for XX power stations usually use seawater as circulating cooling water. The condenser tubes are prone to pitting corrosion in the Cl ion environment, which greatly affects the service life of the condenser tubes. At the same time, high-chromium and high-molybdenum ferritic stainless steel requires good strength and toughness to process and form complex components in actual production. However, due to the high content of Cr and Mo elements, high-chromium and high-molybdenum ferritic stainless steel is prone to precipitate σ (Fe-Cr-Mo) and χ (Fe36Cr12Mo10) brittle phases during the preparation process. These brittle phases greatly deteriorate the strength and toughness and corrosion resistance of the material. Therefore, how to improve the strength and toughness and corrosion resistance in the Cl ion environment is a current research problem in this field.

[0003] In order to improve the strength, toughness and corrosion resistance of high-chromium and high-molybdenum ferritic stainless steel, refining the grains and avoiding the precipitation of brittle phases are effective ways to solve this problem. The existing technology uses alloy elements such as Ce, Al, and Cu to inhibit the precipitation of brittle phases to improve the strength, toughness and corrosion resistance of the material, but other problems still exist. For example, the publication number CN108220812A discloses a rare earth-containing high-strength and plastic super ferritic stainless steel and a preparation method thereof, which utilizes the solid solution effect and grain boundary segregation of the rare earth element Ce to achieve the purpose of grain refinement, but since the expensive rare earth element Ce is added in the invention, its preparation cost is increased; the publication number CN11565624A discloses an ultra-super ferritic stainless steel and a preparation method thereof, adding Al element to inhibit the σ-phase and promote the precipitation of nano-scale Laves phase to achieve the purpose of grain refinement, but the Al element promotes the precipitation of large-sized Nb (C, N) particles, deteriorating the pitting corrosion resistance; the publication number CN118703752A discloses a high-strength and plastic copper-containing super ferritic stainless steel and a production process thereof, optimizing the plasticity and toughness of the super ferritic stainless steel by adding the Cu element, but its strength improvement still cannot meet the strength requirements of some products, and since the addition of Ti stabilizes C and N, large-sized TiN particles are precipitated, reducing the pitting corrosion resistance. Summary of the invention

[0004] The object of the present invention is to provide a method for preparing high-strength, high-toughness, high-corrosion-resistant high-chromium, high-molybdenum ferritic stainless steel, that is, a method for preparing high-strength, high-toughness, high-corrosion-resistant high-chromium, high-molybdenum ferritic stainless steel.

[0005] The present invention is achieved by adopting the following technical solutions: Option 1: A method for preparing high-strength, high-toughness, high-corrosion-resistant high-chromium and high-molybdenum ferrite stainless steel comprises the following steps in sequence: 1) Melting: The weight percentage of each element in the smelting raw material is: 25%≤Cr≤30.0%, 1.5%≤Mo≤4.5%, 0.5%≤Ni≤4.5%, C≤0.015%, N≤0.015%, 0.10%≤Nb≤0.80%, 0.40%≤Cu≤2.0%, Mn≤0.4%, 0.3%≤Si≤1.5%, S≤0.005%, P≤0.005%, O≤0.02%, and Cr+3.3×Mo≥35%, Si≥Nb+0.25%, Cu≥2×Nb+0.20%, and the rest is Fe and unavoidable impurities. After the raw materials are configured according to the above element ratios, they are smelted to obtain molten steel; 2) Forging: Cast the molten steel obtained in step 1) into a billet, open the billet by forging, slowly heat the billet to 1180-1250°C, with a heating rate of 0.5-10°C / min, a forging temperature of 980-1200°C, a forging ratio of 2-4, and obtain a primary forging sample, heat the primary forging sample to 1100-1200°C, keep it warm for 0.2-2h, continue forging until its thickness is 30-50mm, the final forging temperature is ≥950°C, air-cool after forging, and obtain a final forging; 3) Rough rolling: The final forging obtained in step 2) is heated to 1050-1180°C, with a heating rate of ≥20°C / min, and is kept at this temperature for 0.5h-4h before being subjected to multiple passes of rough rolling, with a single pass rough rolling reduction of ≥15% and a total rough rolling reduction of ≥40%; 4) Finish rolling The rough rolled sheet obtained in step 3) is then subjected to multiple passes of finish rolling, with the final rolling temperature being 600-850° C. to obtain a finished rolled sheet; 5) Solution treatment: The finished rolled plate obtained in step 4) is subjected to solution treatment, with a heating temperature of 1010-1150°C and a holding time of 5-120 minutes, followed by rapid cooling immediately with a cooling rate controlled at 50-200°C / s to obtain a hot-rolled solution plate; 6) Cold rolling: The hot-rolled solid solution plate obtained in step 5) is subjected to multiple cold rollings with a cold rolling reduction rate of 50-90% to obtain a cold-rolled plate; 7) Recrystallization annealing: The cold rolled sheet obtained in step 6) is subjected to recrystallization annealing at a temperature of 980-1100° C. for a holding time of 1-60 min, followed by immediate rapid cooling.

[0006] The alloy components of the present invention function as follows: Cr: Cr is the most important alloying element in ferritic stainless steel, and has an important influence on the strength, toughness and corrosion resistance of stainless steel. With the increase of Cr, the strength, toughness and corrosion resistance of stainless steel are significantly improved, but high Cr content will promote the precipitation of brittle phases of σ phase and χ phase, seriously deteriorating the performance of stainless steel. Therefore, it is necessary to control the Cr content between 25% and 30%, and adopt a suitable preparation process to avoid the precipitation of brittle phases.

[0007] Mo: Mo element can improve the corrosion resistance of stainless steel and significantly improve the hardness and mechanical properties of stainless steel. However, Mo will also accelerate the precipitation of brittle phases of σ phase and χ phase, seriously deteriorating the performance of stainless steel. Therefore, the Mo content is limited to between 1.5% and 4.5%, and a suitable preparation process is used to avoid the precipitation of brittle phases.

[0008] Ni: Ni can improve the strength and corrosion resistance of stainless steel, improve the room temperature toughness of stainless steel, and reduce the plastic-to-ductile transition temperature. However, Ni is expensive, so the content is controlled to be 0.5%≤Ni≤4.5%.

[0009] C, N: C and N are the main harmful elements in stainless steel. Since C and N have very low solubility in ferritic stainless steel and diffuse quickly, they are easy to form Cr 23 Harmful precipitated phases such as C6 have a harmful effect on the plasticity, toughness and corrosion resistance of stainless steel. Therefore, it is necessary to add stabilizing elements to combine with C and N to form carbonitrides, and strictly control the content of C and N during the preparation process. The present invention limits C≤0.015% and N≤0.015%.

[0010] Nb: Nb is a stabilizing element in stainless steel. It combines with C and N to form Nb (C, N) compounds, which reduces the precipitation of Cr carbides, further reduces the C and N contents in the matrix, and improves intergranular corrosion resistance and formability. At the same time, Nb can also inhibit the precipitation of Cu-rich phases. However, excessive Nb content will precipitate large-sized NbC particles and reduce pitting corrosion resistance. Therefore, 0.10%≤Nb≤0.80% is controlled.

[0011] Cu: Cu can improve the corrosion resistance of stainless steel and improve the mechanical properties and forming properties of stainless steel. However, if Cu is added too little, it will not have a significant strengthening effect. Too much Cu will precipitate copper-rich phase and reduce the performance of stainless steel. Therefore, it is necessary to control 0.40%≤Cu≤2.0%, and adopt a suitable preparation process to avoid the precipitation of Cu-rich phase.

[0012] Mn, Si: Si element can promote and stabilize fine Laves phase, and improve the corrosion resistance and oxidation resistance of stainless steel. It is usually used as a deoxidizer together with Mn element in the smelting process. Therefore, the present invention controls Mn≤0.4%, 0.3%≤Si≤1.5%.

[0013] P, S: P and S elements exist in stainless steel as inevitable harmful impurity elements and need to be strictly controlled within an extremely low range during the smelting process. The present invention limits S to ≤ 0.005% and P to ≤ 0.005%.

[0014] Principle description: The preparation method of the present invention stabilizes C and N impurity elements, reduces the C and N contents in the matrix, avoids the precipitation of Cr carbides, inhibits the precipitation of Cu-rich phase, and ensures the precipitation of nano-scale Laves phase by adding appropriate Nb elements to ferrite steel; Cu is added to inhibit the precipitation of σ-phase and χ-phase, and promote the precipitation of nano-scale Laves phase, thereby achieving low-temperature hot rolling final rolling, retaining the deformation structure in the hot-rolled plate, and improving the deformation energy storage; the addition of Cu element reduces the stacking fault energy of the material, improves the deformation resistance through solid solution strengthening, retains more dislocations during hot rolling, forms a large number of shear bands and deformation bands, and further provides deformation storage The Cu content is too high to effectively improve the corrosion resistance, and the Cu content is controlled at 0.4-2.0%. A certain amount of Si element is added to the steel, and the Si element dissolves into the Laves phase, increases the precipitation temperature of the Laves phase, promotes and stabilizes the formation of nano-scale Laves phase, and forms a Si-containing passivation film on the surface of the stainless steel, thereby improving the corrosion resistance. In addition, the addition of Si element improves the strength of the material through solid solution strengthening.

[0015] In the specific preparation method, in step 2), the forging blank is slowly heated up, and the heating rate is not higher than 0.5~10 ℃ / min, which can make the elements uniform and avoid the segregation of elements such as Cr, Nb, Cu, etc. If the forging temperature is too high, it will lead to coarse grains. If the forging temperature is too low, the deformation resistance of the forging is too large, the plasticity is poor, and the forging difficulty is large; if the final forging temperature is too low, the deformation resistance of the forging is too large, and cracks are prone to occur. Secondary heating in the middle of forging ensures that a fine grain structure is obtained; the forging is heated in step 3) to obtain a high-temperature steel plate, and the Cr, Cu, Nb, and Si elements segregated at the interface are further dissolved. Through rough rolling with a large reduction rate, a large number of shear bands and deformation bands are formed (see Figure 1), improve deformation energy storage, and provide nucleation points for subsequent Laves phase precipitation; further perform step 4) finishing rolling, the final rolling temperature is 600-850℃, and low-temperature finishing rolling forms a large deformation structure in the steel plate, improves deformation energy storage, and the deformation structure provides points for Laves phase heterogeneous nucleation, and promotes the diffusion of Si elements to Laves phase, controls and optimizes the size and content of Laves phase, and provides appropriate Laves phase for subsequent solid solution recrystallization and grain refinement; step 5) after solution treatment (heating temperature 1010-1150℃, holding time 5-120min), the solid solution process promotes the dissolution and uniform distribution of segregated Cu and Si elements, and completes the recrystallization of the deformation structure in the solid solution plate, and uses the nano-scale Laves phase particles formed in the finishing rolling process to pin the recrystallization grain boundaries to refine the grains, while avoiding the precipitation of σ phase and χ phase (see Figure 2 , Figure 3 ), improve plastic toughness, and prevent cold rolling edge cracking; the hot rolled solid solution plate obtained in step 5) is subjected to step 6) high reduction rate cold rolling, the cold rolling reduction rate is 50-90%, and the large deformation structure is obtained by cold rolling with a large reduction rate, which improves the deformation energy storage. A large number of shear bands, deformation bands, dislocation cells and other microstructures provide nucleation points for recrystallization in the subsequent annealing process; finally, step 9) recrystallization annealing is carried out, the annealing temperature is 980-1100℃, the holding time is 1-60min, the nano-scale Laves phase is stabilized by the solid solution Cu element, and the formed nano-scale Laves phase is used to pin the grain boundary, so that the deformed grains are recrystallized into fine equiaxed grains (see Figure 4 ), and no brittle phase is precipitated, which improves the toughness and corrosion resistance of the material. The nano-scale Laves phase is retained in the recrystallized structure to further improve the strength through precipitation strengthening. In addition, no Ti is added to the steel to avoid the precipitation of TiN particles, reduce the possibility of pitting initiation, and further improve the pitting resistance.

[0016] Furthermore, before step 6) cold rolling, the hot rolled solid solution plate after the solid solution treatment in step 5) needs to be pickled to remove the surface oxide scale, so as to improve the overall quality of the final product.

[0017] Furthermore, after step 3) rough rolling, the obtained rough rolled sheet is heated to 1050-1150° C., and heating again facilitates recrystallization and grain refinement, while preventing the rough rolled sheet from losing too much temperature, which makes it difficult to control the subsequent finishing rolling temperature.

[0018] Furthermore, the cooling rate of the rapid cooling in step 7) is 50-200°C / s.

[0019] Option 2: A method for preparing high-strength, high-toughness, high-corrosion-resistant high-chromium and high-molybdenum ferrite stainless steel comprises the following steps in sequence: 1) Melting: The weight percentage of each element in the smelting raw material is: 25%≤Cr≤30.0%, 1.5%≤Mo≤4.5%, 0.5%≤Ni≤4.5%, C≤0.015%, N≤0.015%, 0.10%≤Nb≤0.80%, 0.40%≤Cu≤2.0%, Mn≤0.4%, 0.3%≤Si≤1.5%, S≤0.005%, P≤0.005%, O≤0.02%, and Cr+3.3×Mo≥35%, Si≥Nb+0.25%, Cu≥2×Nb+0.20%, and the rest is Fe and unavoidable impurities. After the raw materials are configured according to the above element ratios, they are smelted to obtain molten steel; 2) Continuous casting: Continuously casting the molten steel obtained in step 1) into a continuous casting billet, rapidly cooling the continuous casting billet to ≤650°C, then slowly cooling it to 250-400°C at a cooling rate of ≤20°C / h, and grinding it to obtain a casting (controlling the cooling rate to ≤20°C / h, and slow cooling helps to improve the plasticity and toughness of the continuous casting billet and avoid cracking of the casting); 3) Rough rolling: The casting obtained in step 2) is heated to 1180-1280°C, with a heating rate of 0.5-10°C / min, and after being kept warm for 0.5-4h, multiple rough rolling is performed, with a single pass reduction of 15-20%, a total reduction rate of 60-80%, and a rough rolling time of ≤5min to obtain a rough rolled plate (the casting is heated to 1180-1280°C, with a heating rate of 0.5-10°C, which can make the elements uniform and avoid segregation of elements such as Cr, Nb, and Cu; the rough rolling time is ≤5min to avoid excessive temperature drop and ensure the subsequent finishing temperature; 4) Finish rolling The rough rolled sheet obtained in step 3) is then subjected to multiple passes of finish rolling, with the final rolling temperature being 600-850° C. to obtain a finished rolled sheet; 5) Solution treatment: The finished rolled plate obtained in step 4) is subjected to a solution treatment, with a heating temperature of 1010-1200°C and a holding time of 5-120 minutes, followed by rapid cooling immediately with a cooling rate controlled at 50-200°C / s to obtain a solution plate; 6) Cold rolling: The solid solution plate obtained in step 5) is subjected to multiple cold rolling with a cold rolling reduction rate of 50-90% to obtain a cold rolled plate; 7) Recrystallization annealing: The cold rolled sheet obtained in step 6) is subjected to recrystallization annealing at a temperature of 980-1100° C. for a holding time of 1-60 min, followed by immediate rapid cooling.

[0020] Furthermore, before step 6) cold rolling, the hot rolled solid solution plate after the solid solution treatment in step 5) needs to be pickled to remove the surface oxide scale, so as to improve the overall quality of the final product.

[0021] Furthermore, the cooling rate of the rapid cooling in step 7) is 50-200°C / s.

[0022] The application principle of Option 2 is the same as that of Option 1. The only difference is that Option 1 is forging and Option 2 is continuous casting. These are two methods of processing molten steel.

[0023] The beneficial effects of the present invention are as follows: The present invention proposes a high-toughness, high-corrosion-resistant high-chromium, high-molybdenum copper-containing ferritic stainless steel and a preparation method thereof. By adding an appropriate amount of Cu element to the high-chromium, high-molybdenum ferritic stainless steel, controlling the Si element content, and using Nb element monostabilization and selecting a suitable production process, the precipitation of σ and χ brittle phases is suppressed, the precipitation of nano-scale Laves phase is promoted, the precipitation of Cu-rich phase is avoided, low-temperature hot rolling is achieved, the deformation structure is retained in the hot-rolled plate, the deformation energy storage is improved, and the formation of a sufficient amount of fine Laves phase is promoted; at the same time, the solid-solution Cu and Si elements are used to stabilize the nano-scale Laves phase, pin the grain boundary, promote the refinement of recrystallization grains, and combine the solid-solution strengthening effect of Cu and Si elements to improve the strength and toughness of stainless steel. Appropriate Nb is added as a stabilizing element, and Ti element is not added to avoid the precipitation of TiN particles, which reduces the possibility of pitting initiation, and Cu and Si elements are solid-solution matrix, and Cu is attached to the surface to suppress the anodic reaction and Si-containing passivation film formed on the stainless steel surface, thereby improving the pitting resistance in the Cl ion environment. The high-strength, high-corrosion-resistant high-chromium and high-molybdenum ferritic stainless steel of the present invention has a yield strength of 560-660 MPa, a tensile strength of 670-770 MPa, an elongation after fracture of 23-27%, and a corrosion rate of 0.0008-0.0066 mm / a after immersion in 6% FeCl3+1% HCl solution (temperature of 65±1°C) for 216 hours. BRIEF DESCRIPTION OF THE DRAWINGS

[0024] The accompanying drawings, which are incorporated in and constitute a part of this specification, illustrate embodiments consistent with the invention and, together with the description, serve to explain the principles of the invention.

[0025] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, for ordinary technicians in this field, other drawings can be obtained based on these drawings without paying any creative labor.

[0026] Figure 1 Schematic diagram of the shear band microstructure formed after hot rolling in Examples 1-6; Figure 2 Schematic diagram of the nanoscale Laves phase precipitated after solution treatment in Example 1-6; Figure 3 Schematic diagram of the recrystallized structure after solution treatment in Example 1-6; Figure 4 Schematic diagram of the recrystallization structure after recrystallization annealing in Example 1-6; Figure 5 Schematic diagram of large TiN particles precipitated in Comparative Example 1; Figure 6 Schematic diagram of large-sized NbC particles precipitated in Comparative Example 2; Figure 7 This is the corrosion morphology of Example 1-6 after immersion in 6% FeCl3+1% HCl solution (temperature 65±1°C) for 216 hours; Figure 8 This is the corrosion morphology of comparative example 1 after immersion in 6% FeCl3 + 1% HCl solution (temperature 65±1°C) for 72 hours; Fig. 9 This is the corrosion morphology of comparative example 2 after immersion in 6% FeCl3 + 1% HCl solution (temperature 65±1℃) for 72 hours.

[0027] Among them, the shear band microstructure formed after hot rolling, the nanoscale Laves phase precipitated after solution treatment, the recrystallized structure after solution treatment, and the corrosion morphology after immersion for 72 hours in Examples 1-6 are basically the same, so they are replaced by one figure in this application. DETAILED DESCRIPTION

[0028] In order to more clearly understand the above-mentioned objectives, features and advantages of the present invention, the scheme of the present invention will be further described below. It should be noted that the embodiments of the present invention and the features in the embodiments can be combined with each other without conflict.

[0029] In the description, it should be noted that the terms "first" and "second" are only used for descriptive purposes and should not be understood as indicating or implying relative importance. It should be noted that, unless otherwise clearly specified and limited, the terms "installed", "connected" and "connected" should be understood in a broad sense, for example, it can be a fixed connection, a detachable connection, or an integral connection; it can be a mechanical connection or an electrical connection; it can be a direct connection, or it can be indirectly connected through an intermediate medium, or it can be internal communication between two elements. For ordinary technicians in this field, the specific meanings of the above terms can be understood according to specific circumstances.

[0030] In the following description, many specific details are set forth to facilitate a full understanding of the present invention, but the present invention may also be implemented in other ways different from those described herein; it is obvious that the embodiments in the specification are only part of the embodiments of the present invention, rather than all of the embodiments.

[0031] The specific embodiments of the present invention are described in detail below with reference to the accompanying drawings.

[0032] The chemical compositions of the embodiments and comparative examples of the present invention are shown in Table 1. Embodiments 1-6 all adopt Nb single stabilization, and add a certain amount of Cu element to control the Si element content; Comparative Examples 1-2 all adopt Nb and Ti dual stabilization, and a certain amount of Al element is added in Comparative Example 2. Specific preparation process parameters are shown in Table 2.

[0033] Table 1 Chemical composition of high chromium and high molybdenum ferrite stainless steel of various embodiments of the present invention and comparative examples

[0034] Table 2 Main parameters of the preparation process of high chromium and high molybdenum ferrite stainless steel in various embodiments of the present invention and comparative examples

[0035] The pitting corrosion test of ferric chloride solution was based on "ASTM G48-11 Standard Method for Testing Pitting and Crevice Corrosion Resistance of Stainless Steel and Its Alloys Using Ferric Chloride Solution" using 6% FeCl3 + 1% HCl solution at 65 ± 1 ° C. Examples 1-6 were immersed for 216 hours, and Comparative Examples 1-2 were immersed for 72 hours. The results are shown in Table 3. It can be seen from Table 3 that its corrosion resistance in the Cl ion environment is significantly higher than that of Comparative Examples 1-2; at the same time, due to the addition of Ti element in Comparative Example 1, large TiN particles (see Figure 5 , black particles are TiN particles), in comparative example 2, Al element promotes the precipitation of large-sized NbC particles (see Figure 6 , the white rod-shaped particles are NbC particles), its pitting corrosion resistance is greatly deteriorated, and pitting pits appear in both Comparative Example 1 and Comparative Example 2. Figure 8 and 9 As shown, in Examples 1-6, no pitting phenomenon is observed. Figure 7 As shown, its anti-pitting effect is significant; in addition, it can be seen from Table 3 that the yield strength and tensile strength of Examples 1-6 of the present invention are greatly improved compared with Comparative Examples 1-2, and the elongation after fracture is not reduced; Table 3 Properties of high chromium and high molybdenum ferrite stainless steel in various embodiments of the present invention and comparative examples Serial number Yield strength / MPa Tensile strength / MPa Elongation after break / % Corrosion rate / (mm / a) Example 1 685 770 23 0.0066 Example 2 580 685 26 0.0033 Example 3 660 750 24 0.0008 Example 4 600 700 27 0.0041 Example 5 595 705 27 0.0016 Example 6 560 670 25 0.0024 Comparative Example 1 520 655 24 0.213 Comparative Example 2 500 650 25 23.484 The above is only a specific implementation of the present invention, which enables those skilled in the art to understand or implement the present invention. Although detailed descriptions are given with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions recorded in the aforementioned embodiments, or replace some or all of the technical features therein by equivalents; and these modifications or replacements do not make the essence of the corresponding technical solutions deviate from the scope of the technical solutions of the embodiments, and they should all be covered by the protection scope of the claims.

Claims

1. A method for preparing high-toughness, high-corrosion-resistant high-chromium and high-molybdenum ferrite stainless steel, characterized in that: The steps are as follows: 1) Melting: The weight percentage of each element in the smelting raw materials is: 25%≤Cr≤30.0%, 1.5%≤Mo≤4.5%, 0.5%≤Ni≤4.5%, C≤0.015%, N≤0.015%, 0.10%≤Nb≤0.80%, 0.40%≤Cu≤2.0%, Mn≤0.4%, 0.3%≤Si≤1.5%, S≤0.005%, P≤0.005%, O≤0.02%, and Cr+3.3×Mo≥35%, Si≥Nb+0.25%, Cu≥2×Nb+0.20%, and the rest is Fe and unavoidable impurities. After the raw materials are configured according to the above element ratios, they are melted to obtain molten steel; 2) Forging: Cast the molten steel obtained in step 1) into a billet, open the billet by forging, slowly heat the billet to 1180-1250°C, with a heating rate of 0.5-10°C / min, a forging temperature of 980-1200°C, a forging ratio of 2-4, and obtain a primary forging sample, heat the primary forging sample to 1100-1200°C, keep it warm for 0.2-2h, continue forging until its thickness is 30-50mm, the final forging temperature is ≥950°C, air-cool after forging, and obtain a final forging; 3) Rough rolling: The final forging obtained in step 2) is heated to 1050-1180°C, with a heating rate of ≥20°C / min, and is kept at this temperature for 0.5h-4h before being subjected to multiple passes of rough rolling, with a single pass rough rolling reduction of ≥15% and a total rough rolling reduction of ≥40%; 4) Finish rolling The rough rolled sheet obtained in step 3) is then subjected to multiple passes of finish rolling, with the final rolling temperature being 600-850° C. to obtain a finished rolled sheet; 5) Solution treatment: The finished rolled plate obtained in step 4) is subjected to solution treatment, with a heating temperature of 1010-1150°C and a holding time of 5-120 minutes, followed by rapid cooling immediately with a cooling rate controlled at 50-200°C / s to obtain a hot-rolled solution plate; 6) Cold rolling: The hot-rolled solid solution plate obtained in step 5) is subjected to multiple cold rollings with a cold rolling reduction rate of 50-90% to obtain a cold-rolled plate; 7) Recrystallization annealing: The cold rolled sheet obtained in step 6) is subjected to recrystallization annealing at a temperature of 980-1100° C. for a holding time of 1-60 min, followed by immediate rapid cooling.

2. The method for preparing a high-toughness, high-corrosion-resistant high-chromium and high-molybdenum ferrite stainless steel according to claim 1, characterized in that: Before cold rolling in step 6), the hot rolled solid solution plate after solid solution treatment in step 5) needs to be pickled.

3. The method for preparing a high-toughness, high-corrosion-resistant high-chromium and high-molybdenum ferrite stainless steel according to claim 2, characterized in that: After step 3) rough rolling and before step 4) finish rolling, the obtained rough rolled sheet is heated to 1050-1150°C.

4. The method for preparing a high-toughness, high-corrosion-resistant high-chromium and high-molybdenum ferrite stainless steel according to claim 3, characterized in that: The cooling rate of the rapid cooling in step 7) is 50-200°C / s.

5. A method for preparing high-toughness, high-corrosion-resistant high-chromium and high-molybdenum ferrite stainless steel, characterized in that: The steps are as follows: 1) Melting: The weight percentage of each element in the smelting raw material is: 25%≤Cr≤30.0%, 1.5%≤Mo≤4.5%, 0.5%≤Ni≤4.5%, C≤0.015%, N≤0.015%, 0.10%≤Nb≤0.80%, 0.40%≤Cu≤2.0%, Mn≤0.4%, 0.3%≤Si≤1.5%, S≤0.005%, P≤0.005%, O≤0.02%, and Cr+3.3×Mo≥35%, Si≥Nb+0.25%, Cu≥2×Nb+0.20%, and the rest is Fe and unavoidable impurities. After the raw materials are configured according to the above element ratios, they are smelted to obtain molten steel; 2) Continuous casting: The molten steel obtained in step 1) is continuously cast into a continuous casting billet, the continuous casting billet is rapidly cooled to ≤650°C, and then slowly cooled to 250-400°C at a cooling rate of ≤20°C / h, and then ground to obtain a casting; 3) Rough rolling: The casting obtained in step 2) is heated to 1180-1280°C, with a heating rate of 0.5-10°C / min, and is kept warm for 0.5-4h before being subjected to multiple rough rolling, with a single-pass reduction rate of 15-20%, a total reduction rate of 60-80%, and a rough rolling time of ≤5min, thereby obtaining a rough rolled plate; (the casting is heated to 1180-1280°C, with a heating rate of 0.5-10°C, which can homogenize the elements and avoid segregation of elements such as Cr, Nb, and Cu; the rough rolling time is ≤5min to avoid excessive temperature drop and ensure the subsequent finishing temperature; 4) Finish rolling The rough rolled sheet obtained in step 3) is then subjected to multiple passes of finish rolling, with the final rolling temperature being 600-850° C. to obtain a finished rolled sheet; 5) Solution treatment: The finished rolled plate obtained in step 4) is subjected to a solution treatment, with a heating temperature of 1010-1200°C and a holding time of 5-120 minutes, followed by rapid cooling immediately with a cooling rate controlled at 50-200°C / s to obtain a solution plate; 6) Cold rolling: The solid solution plate obtained in step 5) is subjected to multiple cold rolling with a cold rolling reduction rate of 50-90% to obtain a cold rolled plate; 7) Recrystallization annealing: The cold rolled sheet obtained in step 6) is subjected to recrystallization annealing at a temperature of 980-1100° C. for a holding time of 1-60 min, followed by immediate rapid cooling.

6. The method for preparing a high-toughness, high-corrosion-resistant high-chromium and high-molybdenum ferrite stainless steel according to claim 5, characterized in that: Before step 6) cold rolling, the solution plate after the solution treatment in step 5) needs to be pickled.

7. The method for preparing a high-toughness, high-corrosion-resistant high-chromium and high-molybdenum ferrite stainless steel according to claim 6, characterized in that: The cooling rate of the rapid cooling in step 7) is 50-200°C / s.

Citation Information

Patent Citations

  • Rare-earth-containing high-strength plastic super ferrite stainless steel and preparation method thereof

    CN108220812A

  • High chromium content ferrite stainless steel and manufacturing method thereof

    CN101381842A

  • Medium-chromium ferrite stainless steel for automobile with high formability and acidic corrosion resistance as well as manufacturing method thereof

    CN101768702A

  • High-Cr ferrite stainless steel and manufacturing method thereof

    CN102392189A

  • Method for preparing high-chromium and high-molybdenum ferritic stainless steel

    CN112647026A

Cited By

  • Method for improving forming performance of high-chromium and high-molybdenum ferritic stainless steel

    CN121344487A